1978
DOI: 10.1136/pgmj.54.638.779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haematological screening in recurrent aphthae

Abstract: Summary A series of 328 consecutive out-patients with recurrent aphthae were screened for deficiencies of iron, folic acid and vitamin B12, by examination of the peripheral blood, by assays of serum vitamin B12 and corrected whole blood folate, and estimation of the serum iron and total iron binding capacity; deficiencies were demonstrated in 45 patients (13·7%). Of these, 31 were deficient in iron, 15 in folic acid and 11 in vitamin B12; 11 patients had combined deficiencies. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al , 1975; Challacombe et al , 1977a, 1983; Hutcheon et al , 1978; Tyldesley, 1983; Rogers and Hutton, 1986; Field et al , 1987; Porter et al , 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al , 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al , 1975; Challacombe et al , 1977a, 1983; Hutcheon et al , 1978; Tyldesley, 1983; Rogers and Hutton, 1986; Field et al , 1987; Porter et al , 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al , 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
“…RAS-like ulceration can occur in Behcet's disease, however patients with the latter have multisystem disease, particularly affecting (Mittal et al, 1985;Schreiner and Jorizzo, 1987;Arbesfeld and Kurban, 1988;Jankowski et al, 1992;Stratigos et al, 1992). Haematinic (iron, folic acid or vitamin B 12 ) deficiencies may be twice as common in some groups of patients with RAS as in healthy control subjects (Wray et al, 1975;Challacombe et al, 1977aChallacombe et al, , 1983Hutcheon et al, 1978;Tyldesley, 1983;Rogers and Hutton, 1986;Field et al, 1987;Porter et al, 1988). About 20% of patients with RAS may have a haematinic deficiency, although one US study did not report any haematinic problem (Olson et al, 1982).…”
Section: Systemic Factors Predisposing To Rasmentioning
confidence: 99%
“…In several studies, hematinic (iron, folic acid, or vitamin B 1 2) deficiencies have been demonstrated to be twice as common in RAS patients than in controls (Wray et al, 1975;Challacombe et al, 1977aChallacombe et al, , 1983Hutcheon et al, 1978;Tyldesley, 1983;Rogers and Hutton, 1986;Field et al, 1987;Porter et al, 1988). About 20% of patients with RAS may have a hematinic deficiency, though one US study did not report any hematinic problem (Olsen et al, 1982).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Porter et al 20 in his study found that 5% of cases were having folic acid deficiency. Hutcheon et al 21 in his study evaluated 328 patients with RAS and he found hematological deficiencies in 45 patients (13.7%), of which 15(4.57%) were deficient in folic acid. The relation between folic acid and RAS is statically not significant (p=0.174).…”
Section: Results and Observationsmentioning
confidence: 97%